Treatment Strategies in Acute Post-operative Endophthalmitis after Cataract Surgery at a Tertiary Eye Hospital in Nepal: A 5-year Retrospective Review - Suwal, Barsha; Khadka, Deepak; Shrestha, Arjun; Shrestha, Rajan (Nepalese Journal of Ophthalmology, 2021)
Introduction: Despite best possible preventive measures, acute postoperative endophthalmitis (POE) is still the most devastating, sight-threatening complication after intraocular surgery and the most feared complication by treating surgeons.Materials and methods:  It is a retrospective study of 22 eyes diagnosed as acute POE following cataract surgery in the last 5 years (2015-2019), aimed to evaluate the treatment strategies used in its management. Main outcome measures evaluated were rates of repeat intravitreal injection, adjunctive therapeutic regimens, pars plana vitrectomy (PPV) and visual outcome.Results: Twenty one eyes (95.45%) received repeated intravitreal injection. Adjuvant intravitreal steroid was used in 12 eyes (54.54%), oral steroid in 16 eyes (72.72%) and oral antibiotic in 8 eyes (36.36%). PPV was done in 8 eyes (34.78%) and all 8 eyes that underwent PPV had a vision of Hand Movement (HM) close to face. 7 eyes (87.5%) had early PPV within 1 week of diagnosis. The median best corrected visual acuity (BCVA) improved from 1.00 logMar to 0.8 logMar following treatment at 3 months follow up (p= 0.117). Conclusion: Repeat intravitreal injections were commonly employed. Early PPV was performed more commonly regardless of the visual acuity at the time of diagnosis of acute POE.